Sustainable Agritourism in Support of Environmental Sustainability in Rural Areas: A Case Study of Agritourism at Sirahkencong, Ngedirengggo Village, Blitar Regency, East Java, Indonesia - Apsari, Radite Wanudya; Wagistina, Satti; Deffinika, Ifan (Sekolah Pascasarjana Universitas Brawijaya, 2023)
Perseroan Terbatas Perkebunan Nusantara PTPN XII Bantaran administers an afdeeling (a Dutch post-colonial administrative area) focused on one specific business expansion, Agritourism Sirah Kencong. The agritourism area is an excellent destination where a tea plantation landscape stretches up to 55.28 Ha. This tourism object is located 1,179 meters above sea level and is a hydrological footing area. The current research is aimed to: 1) analyze the capacity of the environmental carrying capacity of Agritourism Sirah Kencong; 2) analyze the correlation of environmental sustainability of Agritourism Sirah Kencong; 3) scrutinize the associations between environmental carrying capacity and environmental sustainability in Agritourism Sirah Kencong. Results uncovered that: physical carrying capacity (PCC) contributed to as many as 11,091 tourists per day; real carrying capacity (RCC) 220 per day; and effective carrying capacity (ECC) 174 per day. Following with the assessment, the carrying capacity of Agritourism Sirah Kencong showed similar carrying capacity levels, indicating PCC>RCC>ECC, which means that the board of administrators could still work on ameliorating the number of tourists until the stipulated score limit. However, the maximum number of tourists had ever reached a total of 5,027, which exceeded the limit number of real carrying capacity (RCC) and effective carrying capacity (ECC). In addition, the environmental sustainability of Agritourism Sirah Kencong was assessed based on several indicators, including cleanliness, health, safety, and environmental sustainability (CHSE), and obtained satisfactory recommendation from the certification audit team for CHSE of the Ministry of Tourism and Creative Economy (KEMENPAREKRAF). Furthermore, the research revealed that environmental carrying capacity and sustainability were closely interlinked to ecotourism as it required the tourists’ support for the actualization of sustainable tourism. Keywords: environmental carrying capacity, environmental sustainability, sustainable tourism